Changes in Initial Return Due to Changes in Company Size, Company Age and Debt Equity Ratio: Evidence from the Indonesian Companies Going Public - Ratnasari, Fina; Nursita, Meta; Handayani, Puspita (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This research is an empirical study that aims to examine the influence of these factors, namely company size, company age, and debt to equity ratio (DER). The data used in this study is secondary, using financial statements that have been reported to the Indonesia Stock Exchange. The research sample consisted of 217 companies that conducted IPOs on the Indonesia Stock Exchange in the period 2018 to 2021. Data analysis was performed using multiple linear regression methods to test whether the independent factors had a positive influence on the dependent factor. The existence of companies that conduct IPOs provides an opportunity for investors to obtain initial returns. Initial return is obtained from the difference in price when the investor sells the stock compared to the price when buying it. This research aims to publish accredited national journals as expected output.